Developing human anatomy learning for physical education students using the Pirogov Anatomy Model and Anchored Instruction approach - Susanto, Ratno; Neolaka, Erwin S. (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2025)
This study aims to develop the Pirogov Anatomy Model with an Anchored Instruction approach as an innovation in human anatomy learning for Physical Education students. The background of this research arises from the need for an anatomy learning model that not only emphasizes memorization of body structures but also provides contextual, interactive, and applicable learning experiences relevant to the professional demands in the field of physical education. The Pirogov Anatomy Model utilizes three-dimensional representations of the human body combined with Anchored Instruction, in which learning is guided through contextual scenarios based on real-life problems. Thus, students are encouraged to understand the relationship between anatomical structures, physical activity, sports performance, and health in a more comprehensive way. The research method employed was Research and Development (R&D), consisting of several stages: needs analysis, model design, expert validation, limited trials, and effectiveness testing. The research subjects were Physical Education students enrolled in the Human Anatomy course. Data collection instruments included needs analysis questionnaires, expert validation sheets, and learning outcome tests. The findings indicate that the developed model is valid, practical, and effective in improving students’ conceptual understanding of anatomy. Findings demonstrate a substantial improvement in students’ conceptual understanding. The average pretest score was 62, increasing to 82 on the posttest, resulting in a gain score of 0.53, indicating a moderate to high level of learning effectiveness. Expert evaluations rated the learning design as highly feasible in terms of content accuracy, instructional relevance, and user experience. Students reported improved clarity in identifying anatomical structures and stronger engagement when solving contextual movement-related problems. Overall, the integration of a 3D anatomical visualization tool and anchored, scenario-based learning effectively enhances comprehension of human anatomy in Physical Education contexts and offers a promising model for technology-supported anatomy instruction. Students demonstrated better ability to link anatomical structures with body functions and their application in sports and movement. In conclusion, the Pirogov Anatomy Model with Anchored Instruction offers an innovative alternative learning model that enriches anatomy teaching strategies in higher education, particularly in Physical Education study programs. This model has the potential to improve learning outcomes, critical thinking skills, and the relevance of anatomy knowledge to students’ professional practice